Socio-economic Impact on Displaced Women in Jammu Region: A Sociological View. Issue 1 (June 2021) - Kumar, Sudesh
The present article is based on empirical work carried out in the state of Jammu and Kashmir, where the women were displaced by the dam projects. The main objective of the study is to examine the socio-economic conditions of displaced women after being forcibly displaced from their ancestral home land. Dam projects are the symbol of the economic growth of a nation, but unfortunately, millions of people are being displaced by dam projects in India. What happened to their socio-economic condition? Are they properly resettled? Such questions are always unanswered. The respective government gives only monetary compensation to the whole family. It has been observed that after being forcibly displaced, the displaced women face a lot of socio-economic problems such as poverty, unemployment, being homeless, jobless, dowry issues, domestic violence and health issues.